Active Electrode Material

A mixed phase oxide of Nb, Ti, and additional cations addresses the limitations of graphite and LTO anodes by enhancing lithium ion diffusion and stability, enabling high-power lithium-ion batteries with improved capacity and energy density.

JP2025501335AActive Publication Date: 2025-01-17ECHION TECH LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2024540572
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-05-06
Filing Date
2023-05-05
Publication Date
2025-01-17
Estimated Expiration
2043-05-05

AI Technical Summary

Technical Problem

Existing lithium-ion batteries face limitations in charging rates due to graphite anodes, which can lead to lithium dendrite formation and safety issues, and alternative materials like lithium titanate (LTO) suffer from low specific capacity and reduced energy density despite their safety advantages.

Method used

A mixed phase oxide composed of Nb, Ti, and additional cations (M(III) and/or M(II)) is developed, featuring an interpenetrating mixture of TiNb2O7 and Zn2Nb34O87 phases, enhancing lithium ion diffusion and stability without the need for extensive particle-level engineering.

Benefits of technology

The mixed phase oxide enables high-power batteries with improved capacity and safety at high charging rates, maintaining high capacity at 5C and 10C, and supports the production of lithium-ion batteries with enhanced energy density and reduced manufacturing complexity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025501335000001_ABST
    Figure 2025501335000001_ABST
Patent Text Reader

Abstract

The present invention relates to a mixed phase oxide for use as an active electrode material, for example in a lithium-ion or sodium-ion battery, comprising Nb and Ti, and further comprising M(III) and / or M(II), wherein M(III) is selected from Cr, Al, Ga, and mixtures thereof, and M(II) is selected from Zn, Cu, Mg, and mixtures thereof, the mixed phase oxide comprising an interpenetrating mixture of a first phase and a second phase, the first phase having a crystal structure of TiNb2O7, the second phase having a crystal structure of Zn2Nb 34 O 87 It has a crystal structure of:
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to active electrode materials, methods for making the active electrode materials, and electrodes including the active electrode materials. Such materials are of interest, for example, as anode materials, active electrode materials in metal-ion batteries, such as lithium-ion batteries or sodium-ion batteries. [Background technology]

[0002] Lithium-ion (Li-ion) batteries are a type of commonly used rechargeable battery, with the global market predicted to grow to $200 billion by 2030. Li-ion batteries are the technology of choice for electric vehicles, which meet multiple requirements from technical capabilities to environmental impact, providing a viable path towards a greener automotive industry.

[0003] A typical lithium-ion battery consists of multiple cells connected in series or parallel. Each cell usually consists of an anode (negative electrode) and a cathode (positive electrode), separated by a porous, electrically insulating membrane (called a separator) and immersed in a liquid (called the electrolyte) that allows the transport of lithium ions.

[0004] In most systems, the electrode consists of an active electrode material, meaning that it can chemically react with lithium ions to reversibly store and release them in a controlled manner, optionally mixed with conductive additives (such as carbon) and a polymeric binder. A slurry of these components is coated as a thin film onto a current collector (typically a thin foil of copper or aluminum) so that when dried, it forms the electrode.

[0005] In known Li-ion battery technologies, graphite anodes have safety limitations during battery charging, which is a major obstacle for high-power electronic, automotive and industrial applications. Among various promising alternatives recently proposed, lithium titanate oxide (LTO) and niobium mixed oxide are promising candidates to replace graphite as the optimal active material for high-power and fast-charging applications.

[0006] Batteries relying on graphite anodes are fundamentally limited in terms of charge rate. Under nominal conditions, lithium ions are inserted into the anode active material during charging. At higher charge rates, typical graphite voltage profiles are at high risk of overpotentially driving the potential of the anode site below 0V vs. Li / Li+, resulting in lithium ions instead depositing as lithium metal on the surface of the graphite electrode, a phenomenon known as lithium dendrite electroplating. This results in an irreversible loss of active lithium and therefore a rapid loss of cell capacity. In some cases, these dendritic deposits can grow to such a large size that they can penetrate the battery separator, leading to a short circuit of the cell. This can trigger a catastrophic failure of the cell, resulting in fire or explosion. Therefore, the fastest charging batteries with graphite anodes are limited to charge rates of 5-7C, but often significantly lower.

[0007] Lithium titanate (LTO) anodes have excellent cycle life because they are not subject to dendrite electroplating at high charge rates due to their high potential (1.6 V vs. Li / Li+) and are not subject to significant volume expansion of the active material upon lithium ion intercalation due to their 3D crystalline structure. For these two reasons, LTO cells are generally considered to be safer cells. However, LTO is a relatively poor electronic and ionic conductor, limiting its high rate capacity retention and power capability unless the material is nano-scaled to increase its specific surface area and carbon-coated to increase its electronic conductivity. This particle-level material engineering increases the porosity and specific surface area of ​​the active material, significantly reducing the packing density achievable in the electrode. This results in a lower density electrode and a higher proportion of electrochemically inactive materials (e.g., binders, carbon additives), leading to a significant reduction in gravimetric and volumetric energy density.

[0008] An important indicator of anode performance is the volumetric capacity (mAh / cm) of the electrode. 3 ), i.e., the amount of charge (i.e., lithium ions) that can be stored per unit volume of the anode. This amount, when combined with the cathode and appropriate cell design parameters, is a key factor in determining the overall battery energy density (Wh / L) on a volumetric basis. The volumetric capacity of an electrode is related to the electrode density (g / cm 3 ), the specific capacity of the active material (mAh / g), and the fraction of active material in the electrode. LTO anodes typically have a relatively low specific capacity (~165 mAh / g, compared to ~330 mAh / g for graphite), which accounts for the low electrode density mentioned above (typically 2.0 g / cm 3 This, combined with the small proportion of active material (less than 90%), results in a very small volumetric capacity (300 mAh / cm 3 LTO batteries / cells have a low energy density (less than 1000 kWh) and therefore a high $ cost per kWh for many applications. As a result, LTO batteries / cells are generally limited to niche applications, despite their long cycle life, fast charging capabilities, and high safety.

[0009] Titanium niobium oxide has been proposed for use as an active electrode material. US 2012 / 0052401 A1 describes a compound of the general formula Li x M 1-y Nb y US2015 / 0086872A1 discloses an oxide based on TiNb2O7 with a specific form of carbon coating. US2019 / 0296343A1 and US2014 / 0120404A1 disclose a TiNb2O7 phase and a Ti2Nb 10 O 29 , Nb 14 TiO 37 , TiNb 24 O 64 , and / or mixtures with TiO2 phases. US2021 / 0376307A1 discloses Nb-Ti oxides with a molar ratio of Nb to Ti >2 and containing 100-2,000 ppm of K, Fe, and / or P. EP3667805A1 discloses Ti-containing oxides having a coating layer containing Zn, In, Sn, Pb, Hg, Cu, Cd, Ag, and / or Bi. US2015 / 0125753A1 discloses Nb composite oxides having P compounds on the surface.

[0010] However, there remains a need to identify additional active electrode materials with good properties for use in Li-ion cells, especially for high power / fast charging applications. Identifying these materials, e.g., without the need for extensive particle-level engineering and / or coatings, is an important step towards low-cost battery materials for mass-market adoption. Summary of the Invention

[0011] In a first aspect, the present invention provides a mixed phase oxide for use as an active electrode material, the mixed phase oxide comprises Nb and Ti, and further comprises M(III) and / or M(II); M(III) is selected from Cr, Al, Ga, and mixtures thereof; M(II) is selected from Zn, Cu, Mg, and mixtures thereof; the mixed phase oxide comprises an interpenetrating mixture of a first phase and a second phase; The first phase has a crystal structure of TiNb2O7, and the second phase has a crystal structure of Zn2Nb 34 O 87 It has a crystal structure of:

[0012] The inventors have discovered that the mixed phase oxide according to the first aspect has excellent properties for use in high power batteries designed for high rate charge / discharge, e.g. maintaining high capacity at high rates of 5C and 10C, as shown by this example.

[0013] In a second aspect, the present invention provides an electrode comprising the mixed phase oxide of the first aspect as an active electrode material.

[0014] In a third aspect, the present invention provides a metal-ion battery comprising the electrode of the second aspect. Optionally, the metal-ion battery is a lithium-ion battery or a sodium-ion battery, preferably a lithium-ion battery. Preferably, the electrode forms the anode of the metal-ion battery.

[0015] In a fourth aspect, the present invention provides the use of a mixed phase oxide as defined in the first aspect as an active electrode material in a metal-ion battery, optionally in the anode. Optionally, the metal-ion battery is a lithium-ion battery or a sodium-ion battery, preferably a lithium-ion battery.

[0016] In a fifth aspect, the present invention provides a method of manufacturing an electrode comprising obtaining a mixed phase oxide as defined in the first aspect and depositing the mixed phase oxide on a current collector, thereby forming an electrode. [Brief description of the drawings]

[0017] [Figure 1] XRD of samples 1-8 DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The mixed phase oxides include Nb, Ti, M(III), and M(II). Oxides containing Nb and at least one other cation have a high redox voltage relative to lithium that can exceed 0.8 V, allowing for safe, long-life operation and essential for fast charging of battery cells. In addition, the Nb cation can undergo two redox reactions per atom, resulting in a higher theoretical capacity than, for example, LTO.

[0019] A mixed phase oxide comprises an interpenetrating mixture of a first phase and a second phase, where the first and second phases cannot be separated without destroying the mixed phase oxide.

[0020] The first phase has a crystal structure of TiNb2O7 and the second phase has a crystal structure of Zn2Nb 34 O 87 The interpenetrating mixture of these phases, coupled with the presence of M(III) and / or M(II), defines the crystal structure of each of the two "base" oxides (i.e., TiNb2O7 and pure Zn2Nb 34 O 87 ) are simultaneously modified by substituting elements, e.g., the first phase contains M(III) and / or M(II) in addition to Ti and Nb, and the second phase contains M(III) and / or Ti in addition to M(II) and Nb. The inventors have found that this simultaneous substitution approach improves the properties of each of the "base" oxides, which when combined with a two-phase interpenetrating mixture, provides synergistic benefits compared to the first and second phases separately. For example, the mixed phase oxides of the present invention provide surprisingly improved performance at high rates of 5C and above. Furthermore, the addition of M(II) and / or M(III) cations increases the entropy of the system, promoting the formation of the desired crystal structure.

[0021] The first phase has the crystal structure of TiNb2O7, which is a member of the class of ReO3-derived MOAs known as the Wadsley-Roth crystal structure. 3-xThe Wadsley-Roth crystal structure is considered to be the crystallographic off-stoichiometry of the MO3(ReO3) crystal structure with crystallographic shear, and the MO 3-x As a result, these structures usually contain octahedral [MO6] subunits in their crystal structure. Phases with these structures are believed to have advantageous properties for use as active electrode materials, for example in lithium-ion batteries.

[0022] The open tunnel-like MO3 crystal structure makes it an ideal candidate for high capacity Li-ion storage and high rate of intercalation / deintercalation. The crystallographic off-stoichiometry present in the crystal structure gives rise to Wadsley-Roth crystallographic superstructures. These superstructures, compounded by other properties such as the Jahn-Teller effect and more crystallographic disorder by utilizing multiple mixed cations, stabilize the crystal, keep the tunnels open during intercalation, and allow high lithium diffusion rates (approximately 10 -13 cm 2 s -1 This allows for the ability to achieve very high rates of

[0023] The crystal structure of TiNb2O7 can be described as having a 3x3x∞ crystallographic block structure composed of [MO6] octahedra, where M is Ti or Nb. The crystal structure is generally monoclinic. The crystal structure of TiNb2O7 can be found in PDF card 00-039-1407. The unit cell parameters a, b, and c can be: a 17.66-17.74 Å, preferably 17.68-17.72 Å; b 3.77-3.84 Å, preferably 3.79-3.82 Å; and c 11.86-11.94 Å, preferably 11.88-11.92 Å. The crystal structure of the first phase has unit cell parameters α and γ, each about 90°, preferably α=γ=90°, and β 95.30-95.37°, preferably 95.32-95.36°.

[0024] Without wishing to be bound by theory, the inventors believe that the Wadsley-Roth crystal structure contains larger cations, such as Zn 2+ It is believed that the addition of may change the lattice parameters of the structure, thereby allowing better diffusion of lithium ions. Furthermore, doping with such non-redox active cations may prevent the octahedron from tilting during charging and discharging, providing structural stability.

[0025] The second phase is Zn2Nb 34 O 87 This also has the crystal structure of MO derived from ReO3. 3-x It can be considered to have the Wadsley-Roth crystal structure. Zn2Nb 34 O 87 The crystal structure of can be described as having a 3x4x∞ crystallographic block structure composed of [MO6] octahedra, where M is Zn or Nb. When M(II) is absent, the crystal structure Zn2Nb 34 O 87 is realized with M(III) or Ti employing Zn sites. It is believed that the large block size is advantageous for fast lithium insertion and removal compared to other Wadsley-Roth structures with smaller octahedral block sizes, and may lead to greater stability than those with larger octahedral block sizes. The Zn octahedra may be randomly distributed in the structure or may prefer specific locations such as the edges or corners of the blocks. This is equal to 2 / 3 of one Zn cation per block.

[0026] The crystal structure of the second phase may be monoclinic or orthorhombic, or may be considered a mixture of monoclinic and orthorhombic. 34 O 87 The crystal structure of can be found in ICDD Crystallographic Database Entry PDF Card 00-013-0317. 34 O 87 The crystal structure of can be found in PDF card 04-021-7859.

[0027] When refined to a monoclinic structure, the unit cell parameters a, b, and c may be: a 15.52-15.58 Å, preferably 15.53-15.57 Å; b 3.79-3.84 Å, preferably 3.80-3.83 Å; c 20.53-20.66 Å, preferably 20.54-20.65 Å; the unit cell parameters α and γ are each about 90°, preferably α=γ=90°; and β is 113.00-113.75°, preferably 113.06-113.69°.

[0028] The crystal structure of the phases can be determined by analysis of X-ray diffraction (XRD) patterns obtained using Cu K-α radiation, as is widely known. For example, the XRD pattern obtained from a particular material can be compared to known XRD patterns to confirm the crystal structure via a public database, for example the ICDD Crystallography Database. Rietveld and Pawley analyses can also be used to determine the crystal structure of a material, in particular the unit cell parameters. Thus, the crystal structures of the first and second phases can be determined by XRD.

[0029] The XRD pattern of the mixed phase oxide preferably exhibits a peak A at 2θ=26.0±0.1°, which is assigned to the first phase. The XRD pattern of the mixed phase oxide preferably exhibits a peak B at 2θ=24.9±0.1°, which is assigned to the second phase. The intensity I of peak A A Intensity of peak B against I B The ratio of B / I A ≦0.4, or 0.01≦I B / I A ≦0.25, or preferably, 0.05≦I B / I A In certain instances, the ratio may be 0.07≦I B / I A ≦0.16. The peak intensity ratio can be conveniently calculated using the normalized heights of peaks A and B.

[0030] ​The weight ratio of the first phase to the second phase can be from 199:1 to 1:1, or from 99:1 to 3:1, or from 50:1 to 8:1. The weight ratio of the phases in the mixed phase oxide can be determined by refinement of the XRD pattern of the mixed phase oxide. The target weight ratio can be obtained by controlling the relative amounts of elemental precursors used in the synthesis.

[0031] Other phases may be present in the mixed phase oxide. For example, the first phase and the second phase may form at least 80% by weight, at least 90% by weight, or at least 95% by weight of the mixed phase oxide. The first phase and the second phase may form substantially all of the mixed phase oxide, for example with less than 1% by weight of other phases. Preferably, the first phase forms at least 85% by weight, or at least 90% by weight, or at least 92% by weight of the mixed phase oxide.

[0032] Nb is preferably the predominant cation present in the mixed phase oxide, for example the mixed phase oxide may contain 66-80 at% Nb, or 66.5-75 at%, or 66.9-69.9 at% Nb based on total cations.

[0033] The mixed phase oxide may contain 33-17 at% Ti, or 33.1-24 at%, or 33.2-30 at% Ti relative to all cations.

[0034] The mixed phase oxide may contain >0-1 at.%, or 0.01-0.4 at.%, or 0.01-0.2 at.% M(III) based on total cations.

[0035] The mixed phase oxide may contain >0-2 at.%, or 0.01-1 at.%, or 0.02-0.5 at.% M(II) based on total cations.

[0036] The combined amount of M(III) and M(II) may be ≧0.05 at%, ≧0.5 at%, or ≧0.6 at% relative to the amount of Nb.

[0037] The atomic ratio of Ti:Nb may be at least 0.3:1, or at least 0.4:1, or between 0.42:1 and 0.5:1.

[0038] It will be appreciated that the amounts of Nb, Ti, M(III), and / or M(II) can be combined to further define the mixed phase oxide.

[0039] M(III) represents a cation that usually has an oxidation state of 3+ in the oxide. M(III) is selected from Cr, Al, Ga, and mixtures thereof, or Cr, Al, and mixtures thereof. Preferably, M(III) is Cr.

[0040] M(II) represents a cation that usually has an oxidation state of 2+ in the oxide. M(II) is selected from Zn, Cu, Mg, and mixtures thereof, or Zn, Cu, and mixtures thereof. Preferably, M(II) is Zn.

[0041] Preferably, the mixed phase oxide comprises M(III), especially when M(III) is Cr and M(II) is Zn, and most preferably comprises M(III) and M(II).

[0042] The mixed phase oxide may optionally further comprise at least one additional element. Optionally, the additional element is selected from Zr, Hf, V, Fe, Ta, Mo, W, Mn, Co, Ni, Cd, B, Si, Sn, P, and mixtures thereof, or Zr, V, Fe, Mo, W, Mn, Co, Ni, Cd, B, Si, P, and mixtures thereof, or preferably Zr, V, Fe, Mo, W, Cu, P, and mixtures thereof. The at least one additional element may be present in an amount of ≦1.5 at% or less, or 0.01-1.0 at% relative to the total cations. The at least one additional element may be present in a total amount of ≦5 at%, or ≦1 at%, or 0.01-0.5 at% relative to the amount of Nb.

[0043] Where M(III) and / or M(II) are limited to the preferred elements, the optional additional elements may include alternative M(III) and / or M(II) elements. For example, where M(III) is Cr and M(II) is Zn, the at least one additional element may be further selected from Al, Ga, Cu, Mg, and mixtures thereof.

[0044] Alternatively, the cations of the mixed phase oxide may consist of Nb, Ti, M(III), and / or M(II), or may consist of Nb, Ti, M(III), and M(II).

[0045] The mixed phase oxides can further include Li and / or Na, which can be reversibly intercalated in situ when the oxides function as active electrode materials in metal ion batteries.

[0046] Advantageously, it has been found that mixed phase oxides can be formed by simple solid-state synthesis methods, as shown by this example. Moreover, the improved properties obtained by the interpenetrating mixture of the first and second phases are obtained without the need for particle-level engineering, for example, without the need to form a core / shell structure, which may normally require complex synthesis. Thus, preferably, the interpenetrating mixture of the first and second phases does not form a core / shell structure. For example, the interpenetrating mixture of the first and second phases does not form a structure in which the first phase forms a shell portion and the second phase forms a core portion surrounded by the shell portion.

[0047] The mixed phase oxide is preferably granular. The mixed phase oxide has a diameter of D in the range of 0.1 to 100 μm, or 0.5 to 50 μm, or 1 to 20 μm. 50 These particle sizes are advantageous because they are easy to process and manufacture into electrodes. Furthermore, these particle sizes eliminate the need to use complex and / or expensive methods to produce nano-sized particles. Nano-sized particles (e.g., D of 100 nm or less) can be used. 50Particles having a particle size of 0.1 mm or less are usually more complicated to synthesize and require additional safety considerations.

[0048] The mixed phase oxide has a D of at least 0.05 μm, or at least 0.1 μm, or at least 0.5 μm, or at least 1 μm. 10 D 10 Maintaining the particle size in these ranges reduces the potential for parasitic reactions in Li-ion cells due to reduced surface area and allows for easier processing, requiring less binder in the electrode slurry.

[0049] Mixed phase oxides are those with a diameter of 200 μm or less, 100 μm or less, 50 μm or less, or 20 μm or less D 90 D 90 By maintaining the particle size within these ranges, the proportion of the particle size distribution at larger particle sizes is minimized, making it easier to fabricate the material into a homogenous electrode.

[0050] The term "particle size" refers to the equivalent spherical diameter (esd), i.e., the diameter of a sphere having the same volume as a given particle, the volume of the particle being understood to include the volume of any intraparticle pores. n " and "D n The term "particle size" refers to the diameter below which n% by volume of the particle population is found. 50 " and "D 50 The term "particle size" refers to the volume-based median particle size below which 50% by volume of the particle population are found. It will be understood that where the material contains primary crystallites aggregated into secondary particles, the particle size refers to the diameter of the secondary particles. Particle size can be determined by laser diffraction. Particle size can be measured in accordance with ISO 13320:2009, e.g., using Mie theory.

[0051] Mixed phase oxides are 0.1 to 100 m 2 / g, or 0.25 to 50m 2 / g, or 0.5 to 20m 2The mixed phase oxide may have a BET surface area in the range of 0.1 to 1.0 μm / g. In general, a low BET surface area is preferred to minimize reaction of the mixed phase oxide with the electrolyte, e.g., to minimize the formation of a solid electrolyte interphase (SEI) layer during the first charge-discharge cycle of an electrode containing the material. However, if the BET surface area is too low, a large portion of the mixed phase oxide will not be accessible to metal ions in the surrounding electrolyte, resulting in unacceptably low charge rates and capacities.

[0052] The term "BET surface area" refers to the surface area per unit mass calculated from measurements of the physical adsorption of gas molecules on a solid surface using the Brunauer-Emmett-Teller theory. For example, the BET surface area can be determined in accordance with ISO9277:2010.

[0053] The mixed phase oxides may have crystallite sizes greater than 180 nm, or greater than 200 nm, or greater than 225 nm, or preferably greater than 250 nm. The crystallite sizes may range from 180 nm to 20 μm, or 200 nm to 10 μm, or 225 nm to 5 μm, or 250 nm to 3 μm. It is believed that in these crystallite size ranges, there are fewer grain boundaries in the material and therefore less interfacial resistance, improving ion transport compared to materials with smaller crystallites. Higher density particles and denser electrodes can also be produced with larger crystallite sizes. Crystallite size can be conveniently measured by the Scherrer method using crushed Si crystals as a standard.

[0054] In a powder X-ray diffraction pattern, the shape of the diffraction peaks is determined by the convolution of the line profile produced by the diffractometer optics (instrumental contribution) with that produced by the sample (sample-dependent peak broadening). Finite size diffracting crystallites in a sample contribute to the width of the diffraction peaks. The instrumental contribution can be taken into account, and the diffraction peak width can then be used to determine the volume-weighted average crystallite diameter by using Scherrer's equation. Scherrer's equation correlates the width of a diffraction peak at a given Bragg angle with the minimum crystallite diameter.

number

[0055] Preferably, the Scherrer method is used to determine the volume-weighted average crystallite size of the sample, and the instrument contribution can be determined from the measurement of a standard sample. The standard sample should be a crystalline material with a large crystallite size, e.g., an average crystallite size >1 μm, and ideally has a Bragg peak at the same angle as the peak selected for analysis of the test sample. LaB6 (e.g., NIST SRM 660C) or crushed Si crystals (e.g., NIST SRM 640C) are often used. The sample peak selected for analysis should be a single Bragg reflection, preferably the peak with the highest scattering intensity. The full width at half maximum of the peak is measured by finding the point of the diffraction peak where the scattering intensity is halfway between the background intensity and the maximum intensity of the peak, and measuring the difference in the values ​​of the 2θ Bragg angle of the peak at these scattering intensity values.

[0056] Preferably, the standard and test samples should be measured using the same conditions on the same instrument. The scan speed and step size of the diffraction measurement should be such that the peak intended to be investigated contains at least 8 data point measurements above the half-maximum point, and the maximum intensity point of the peak has at least 10 times the intensity of the background.

[0057] Transmission electron microscopy (TEM) examination can further be used to confirm the crystallite size determined by the Scherrer method. 50Grains with an overall size close to 0.01 mm are examined by selected area electron diffraction (SAED) to investigate the degree of crystalline domains within the grain. If the zone axes are aligned and a clear diffraction pattern is obtained, a spatial map can be created by measuring the diffraction pattern at spatial intervals until a grain boundary is encountered.

[0058] The mixed phase oxide may be coated with carbon, for example, to improve the electrical conductivity of the surface and / or to prevent reaction with the electrolyte.

[0059] The mixed phase oxide may have a protective coating, optionally comprising niobium oxide, aluminum oxide, zirconium oxide, organic or inorganic fluorides, organic or inorganic phosphates, titanium oxide, lithiated versions thereof, and mixtures thereof.

[0060] The electrode of the second embodiment is typically in the form of an electrode composition comprising a mixed phase oxide in electrical contact with a current collector, the current collector usually being a metal foil such as copper or aluminum foil.

[0061] Optionally, the mixed phase oxide forms at least 25%, 50%, or 75% by weight of the total active electrode material of the electrode. The mixed phase oxide may form the only active electrode material of the electrode.

[0062] The electrode composition may further comprise at least one other component selected from a binder, a conductive additive, a different active electrode material (e.g., additional mixed phase oxides as defined herein), and mixtures thereof. For example, one electrode composition comprises about 92 wt. % mixed phase oxide, about 5 wt. % conductive additive (e.g., carbon black), and about 3 wt. % binder (e.g., poly(vinyl difluoride)), based on the total dry weight of the electrode composition.

[0063] Examples of suitable binders include polyvinylidene fluoride and its copolymers (PVDF), polytetrafluoroethylene (PTFE) and its copolymers, polyacrylonitrile (PAN), poly(methyl)methacrylate or poly(butyl)methacrylate, polyvinyl chloride (PVC), polyvinyl formal, polyetheramide, polymethacrylic acid, polyacrylamide, polyitaconic acid, polystyrene sulfonic acid, polyacrylic acid (PAA) and its alkali metal salts, modified polyacrylic acid (mPAA) and its alkali metal salts, cellulosic polymers, carboxymethylcellulose (CMC), modified carboxymethylcellulose (mCMC), sodium carboxymethylcellulose (Na-CMC), polyvinyl alcohol (PVA), alginates and their alkali metal salts, butadiene acrylonitrile rubber (NBR), hydrogenated form of NBR (HNBR), styrene butadiene rubber (SBR), and polyimides. The binder can be present in the electrode composition at 0 to 30 wt%, or 0.1 to 10 wt%, or 0.1 to 5 wt%, based on the total dry weight of the electrode composition.

[0064] The conductive additive is preferably a non-active material that is included to improve electrical conductivity between active electrode materials and between the active electrode material and the current collector. The conductive additive can be appropriately selected from graphite, carbon black, carbon fiber, vapor grown carbon fiber (VGCF), carbon nanotubes, graphene, acetylene black, ketjen black, metal fiber, metal powder, and conductive metal oxide. Preferred conductive additives include carbon black and carbon nanotubes. The conductive additive can be present in the electrode composition in an amount of 0 to 20 wt%, 0.1 to 10 wt%, or 0.1 to 5 wt%, based on the total dry weight of the electrode composition.

[0065] The mixed phase oxide can be present in the electrode composition at 100-50 wt%, 99.8-80 wt%, or 99.8-90 wt%, based on the total dry weight of the electrode composition. When the active electrode material is present at 100 wt% of the electrode composition, it can be used as a solid electrode.

[0066] If a different active electrode material is present in addition to the mixed phase oxide, it may be selected from lithium titanium oxide, titanium niobium oxide, different mixed phase oxides, graphite, hard carbon, soft carbon, silicon, doped versions thereof, and mixtures thereof.

[0067] The mixed phase oxide can be combined with lithium titanium oxide to form the active electrode material.

[0068] The lithium titanium oxide preferably has a spinel or ramsdellite crystal structure, for example as determined by X-ray diffraction. An example of a lithium titanium oxide having a spinel crystal structure is Li4Ti5O 12 An example of a lithium titanium oxide with the ramsdellite crystal structure is Li2Ti3O7. These materials have been shown to have excellent properties for use as active electrode materials. Thus, lithium titanium oxide is Li4Ti5O 12 and / or Li2Ti3O7. Lithium titanium oxide may have a crystal structure as determined by X-ray diffraction corresponding to Li4Ti5O 12 , Li2Ti3O7, and mixtures thereof. The lithium titanium oxide may be doped with additional cations or anions. The lithium titanium oxide may be oxygen deficient. The lithium titanium oxide may include a coating, optionally the coating being selected from carbon, polymer, metal, metal oxide, metalloid, phosphate, and fluoride. The lithium titanium oxide may be synthesized by conventional ceramic techniques, such as solid state synthesis or sol-gel synthesis. Alternatively, the lithium titanium oxide may be obtained from a commercial supplier.

[0069] The lithium titanium oxide is preferably granular. The lithium titanium oxide has a diameter of D in the range of 0.1 to 50 μm, or 0.25 to 20 μm, or 0.5 to 15 μm. 50The lithium titanium oxide may have a particle size of at least 0.01 μm, or at least 0.1 μm, or at least 0.5 μm. 10 The lithium titanium oxide may have a particle size of 100 μm or less, 50 μm or less, or 25 μm or less. 90 D 90 Maintaining the particle size in this range improves the packing of the lithium titanium oxide particles in admixture with the mixed phase oxide particles.

[0070] Lithium titanium oxide is typically used in battery anodes with small particle sizes due to the low electronic conductivity of the material. In contrast, the mixed phase oxides defined herein typically have higher lithium ion diffusion coefficients than lithium titanium oxide and can be used with larger particle sizes. Advantageously, in the composition, the lithium titanium oxide can have a smaller particle size than the mixed phase oxide, e.g., the D of the mixed phase oxide. 50 D of lithium titanium oxide versus particle size 50 is in the range of 0.01:1 to 0.9:1, or 0.1:1 to 0.7:1, in which case the smaller lithium titanium oxide particles can be accommodated in the voids between the larger mixed phase oxide particles, increasing the packing efficiency of the composition.

[0071] Lithium titanium oxide is 0.1 to 100m 2 / g, or 1 to 50m 2 / g, or 3 to 30m 2 The nanoparticles may have a BET surface area in the range of 1 / g.

[0072] The mass ratio of lithium titanium oxide to the mixed phase oxide may be in the range of 0.5:99.5 to 99.5:0.5, preferably in the range of 2:98 to 98:2. In one embodiment, the active electrode material comprises a higher proportion of lithium titanium oxide than the mixed phase oxide, for example a mass ratio of at least 2:1, at least 5:1, or at least 8:1. Advantageously, this allows the mixed phase oxide to be gradually introduced into existing electrodes based on lithium titanium oxide without the need to significantly change the manufacturing technology, providing an efficient way to improve the properties of existing electrodes. In another embodiment, the active electrode material comprises a higher proportion of mixed phase oxide than lithium titanium oxide, for example a mass ratio of lithium titanium oxide to the mixed phase oxide of less than 1:2, or less than 1:5, or less than 1:8. Advantageously, this allows the cost of the active electrode material to be reduced by replacing part of the mixed phase oxide with lithium titanium oxide.

[0073] The mixed phase oxides can be combined with niobium oxides to form active electrode materials. 12 O 29 , NbO2, NbO and Nb2O5. Preferably, the niobium oxide is Nb2O5.

[0074] Niobium oxide is, for example, a crystalline structure of an oxide composed of Nb and O, for example, Nb 12 O 29 , NbO2, NbO, and Nb2O5. The niobium oxide may be oxygen deficient. The niobium oxide may include a coating, optionally selected from carbon, polymer, metal, metal oxide, metalloid, phosphate, and fluoride.

[0075] Niobium oxide is Nb as determined by X-ray diffraction. 12 O 29, NbO2, NbO, or Nb2O5 crystal structure. For example, the niobium oxide can have an orthorhombic Nb2O5 crystal structure or a monoclinic Nb2O5 crystal structure. Preferably, the niobium oxide has a monoclinic Nb2O5 crystal structure, and most preferably has a H-Nb2O5 crystal structure. Further information regarding the crystal structure of Nb2O5 can be found in Griffith et al., J. Am. Chem. Soc. 2016, 138, 28, 8888-8899. The niobium oxide can be synthesized by conventional ceramic techniques, such as solid-state synthesis or sol-gel synthesis. Alternatively, the niobium oxide can be obtained from a commercial supplier.

[0076] The niobium oxide is preferably in the form of particles. The niobium oxide has a diameter of D in the range of 0.1 to 100 μm, or 0.5 to 50 μm, or 1 to 20 μm. 50 The niobium oxide may have a particle size of at least 0.05 μm, or at least 0.5 μm, or at least 1 μm. 10 The niobium oxide may have a particle size of 100 μm or less, 50 μm or less, or 25 μm or less. 90 D 90 Maintaining the particle size in this range improves the packing of the niobium oxide particles in the mixture with the mixed phase oxide particles.

[0077] Niobium oxide is 0.1 to 100m 2 / g, or 1 to 50m 2 / g, or 1 to 20m 2 The nanoparticles may have a BET surface area in the range of 1 / g.

[0078] The mass ratio of niobium oxide to mixed phase oxide may be in the range of 0.5:99.5 to 99.5:0.5, or in the range of 2:98 to 98:2, or preferably in the range of 15:85 to 35:55.

[0079] The present invention also provides the use of a mixed phase oxide as defined herein in the anode of a metal ion battery, optionally the metal ion battery being a lithium ion battery or a sodium ion battery, preferably a lithium ion battery, including liquid based batteries, polymer based batteries, semi-solid based batteries and all solid based batteries.

[0080] A further embodiment of the invention is an electrochemical device comprising an anode, a cathode, and an electrolyte disposed between the anode and the cathode, the anode comprising the mixed phase oxide according to the first aspect of the invention, and optionally the electrochemical device being a metal ion battery such as a lithium ion battery or a sodium ion battery. Preferably, the electrochemical device is a lithium ion battery having a reversible anode active material specific capacity of greater than 230 mAh / g at 23 mA / g, such that the battery can be charged and discharged at current densities for the anode active material of 200 mA / g or more, or 1000 mA / g or more, or 2000 mA / g or more, or 4000 mA / g or more, while retaining more than 70% of the initial cell capacity at 23 mA / g. It has been found that the use of the active electrode material of the first aspect of the invention may enable the fabrication of lithium ion batteries having this combination of properties, representing lithium ion batteries particularly suitable for use in applications where high charge and discharge current densities are desired. In particular, the examples have shown that the active electrode material according to the first aspect of the invention has excellent capacity at high C-rates.

[0081] The mixed phase oxide can be synthesized by conventional ceramic techniques. For example, it may be produced by one or more of solid synthesis or sol-gel synthesis, preferably by solid synthesis using particulate precursors as shown by the examples. The mixed phase oxide can be further synthesized by one or more of commonly used alternative techniques such as hydrothermal or microwave hydrothermal synthesis, solvothermal or microwave solvothermal synthesis, co-precipitation synthesis, spark or microwave plasma synthesis, combustion synthesis, electrospinning, spray pyrolysis, chemical vapor deposition, atomic layer deposition, and mechanical alloying.

[0082] The mixed phase oxide can be obtained by a method including the steps of obtaining one or more precursor materials, mixing the precursor materials to form a precursor material mixture, and heat treating the precursor material mixture at a temperature range of 800°C to 1350°C or 1000°C to 1300°C, thereby obtaining the mixed phase oxide.

[0083] The mixed phase oxide may be modified to include at least one electronegative element, partially replacing the oxygen anions with alternative anions selected from F, Cl, Br, I, N, S, Se, and mixtures thereof, or F, Cl, N, S, and mixtures thereof, or preferably F, N, and mixtures thereof. The at least one electronegative element may be present in a total amount of ≦5 at% or ≦1 at% relative to the amount of O. The electronegative element may be introduced by mixing the mixed phase oxide with a precursor containing the electronegative element to obtain a further precursor material mixture, and heat treating the further precursor material mixture, optionally under reducing conditions, at a temperature range of 300-1200° C. or 800-1100° C., thereby obtaining the mixed phase oxide containing the further electronegative element.

[0084] For example, to obtain a N-containing mixed phase oxide, the method may further include mixing the mixed phase oxide with a N-containing precursor (e.g., melamine or urea) to obtain a further precursor material mixture, and heat treating the further precursor material mixture under reducing conditions (e.g., under N) at a temperature range of 300-1200°C, thereby obtaining a N-containing mixed phase oxide.

[0085] For example, to obtain a mixed phase oxide containing F, the method may further include mixing the mixed phase oxide with a precursor containing F (e.g., polyvinylidene fluoride, or NHF) to obtain a further precursor material mixture, and heat treating the further precursor material mixture under oxidizing conditions (e.g., in air) at a temperature range of 300-1200°C, thereby obtaining a mixed phase oxide containing F.

[0086] The method may include the further step of heat treating the mixed phase oxide under reducing conditions in the temperature range of 400-1350° C. or 800-1250° C., thereby inducing oxygen vacancies in the mixed phase oxide.

[0087] The precursor materials for making the mixed phase oxides can include one or more metal oxides, metal hydroxides, metal salts, or ammonium salts. For example, the precursor materials can include one or more metal oxides or metal salts of different oxidation states and / or different crystal structures. Examples of suitable precursor materials include, but are not limited to, Nb2O5, Nb(OH)5, niobic acid, NbO2, ammonium oxalate niobate, NH4H2PO4, (NH4)2PO4, (NH4)3PO4, P2O5, H3PO3, Ta2O5, WO3, ZrO2, TiO2, MoO3, V2O5, ZrO2, CuO, ZnO, Al2O3, K2O, KOH, CaO, GeO2, Ga2O3, SnO2, CoO, Co2O3, Fe2O3, Fe3O4, Cr2O3, MnO, MnO2, NiO, Ni2O3, H3BO3, ZnO, Li2CO3, Na2CO3, H3BO3, NiO, Mg5(CO3)4(OH)2.5H2O, and MgO. The precursor material may not include a metal oxide or may include an ion source other than an oxide. For example, the precursor material may be a metal salt (e.g., NO3 - , SO3 - ) or other compounds (e.g., oxalates, carbonates). When replacing the oxygen anion with other electronegative anions, the precursors may include one or more organic compounds, polymers, inorganic salts, organic salts, gases, or ammonium salts, examples of which include melamine, NH4HCO3, NH3, NH4F 、 These include, but are not limited to, PVDF, PTFE, NH4Cl, NH4Br, NH4I, Br2, Cl2, I2, ammonium oxychloridamide, and hexamethylenetetramine.

[0088] Some or all of the precursor materials may be particulate materials. If they are particulate materials, preferably they have a diameter of less than 20 μm, for example a D of 250 nm to 20 μm. 50Obtaining particulate material with such a particle size can help promote more intimate mixing of the precursor materials, thereby resulting in a more efficient solid-state reaction during the heat treatment step. However, it is not essential that the precursor materials have an initial particle size of less than 20 μm, since the particle size of one or more of the precursor materials can be mechanically reduced during the step of mixing the precursor materials to form the precursor material mixture.

[0089] The step of mixing the precursor materials to form the precursor material mixture and / or further precursor material mixture may be carried out by a process selected from dry or wet / planetary solvating ball milling, rolling ball milling, high energy ball milling, bead milling, pin milling, a classification step, high shear milling, air jet milling, steam jet milling, planetary mixing, high shear mixing, impact mixing, powder mixing, and / or impact milling. The force used for mixing / milling may depend on the morphology of the precursor materials. For example, if some or all of the precursor materials are in a larger particle size (e.g., D greater than 20 μm), the mixing / milling force may be increased by 100%. 50 When the precursor material has a particle size of 20 μm or less, the milling force can be selected to reduce the particle size of the precursor material mixture such that the particle size of the precursor material mixture is reduced to 20 μm or less in diameter. A particle size of 20 μm or less of the precursor mixture can more efficiently promote solid-state reaction of the precursor materials of the precursor material mixture during the heat treatment step. Solid-state synthesis can also be performed on pellets formed at high pressure (greater than 10 MPa) from the precursor powder.

[0090] The step of heat treating the precursor material mixture and / or the further precursor material mixture may be carried out for a time period between 1 hour and 24 hours, more preferably between 3 hours and 18 hours. For example, the heat treating step may be carried out for 1 hour or more, 2 hours or more, 3 hours or more, 6 hours or more, or 12 hours or more. The heat treating step may be carried out for 24 hours or less, 18 hours or less, 16 hours or less, or 12 hours or less.

[0091] The step of heat treating the precursor material mixture may be carried out in a gas atmosphere, preferably air. Suitable gas atmospheres include air, N2, Ar, He, CO2, CO, O2, H2, NH3 and mixtures thereof. The gas atmosphere may be a reducing atmosphere. If it is desired to create an oxygen deficient material, preferably the step of heat treating the precursor material mixture is carried out in an inert or reducing atmosphere.

[0092] The step of heat treating the further precursor material mixture may be carried out under reducing conditions, including under an inert gas such as nitrogen, helium, argon, or under a mixture of an inert gas and hydrogen, or under vacuum. Preferably, the step of heat treating the further precursor material mixture comprises heating under an inert gas.

[0093] The further step of optionally heat treating the mixed phase oxide and / or the mixed phase oxide containing additional electronegative anions under reducing conditions can be carried out for a time period between 0.5 hours and 24 hours, more preferably between 2 hours and 18 hours. For example, the heat treatment step can be carried out for 0.5 hours or more, 1 hour or more, 3 hours or more, 6 hours or more, or 12 hours or more. The further step of heat treatment can be carried out for 24 hours or less, 18 hours or less, 16 hours or less, or 12 hours or less. Reducing conditions include under an inert gas such as nitrogen, helium, argon, or under a mixture of inert gas and hydrogen, or under a vacuum. Preferably, the heating under reducing conditions includes heating under an inert gas.

[0094] In some methods, it may be beneficial to carry out a two-step heat treatment. For example, the precursor material mixture and / or the further precursor material mixture may be heated at a first temperature for a first time, followed by heating at a second temperature for a second time. Preferably, the second temperature is higher than the first temperature. Such a two-step heat treatment may assist the solid-state reaction to form the desired crystal structure. This may be carried out consecutively or with an intermediate regrinding step.

[0095] The method may include one or more post-treatment steps after the formation of the mixed phase oxide. In some cases, the method may include a post-treatment step of heat treating the mixed phase oxide, sometimes referred to as "annealing". This post-treatment heat treatment step may be performed in a different gas atmosphere than the step of heat treating the precursor material mixture to form the mixed phase oxide. The post-treatment heat treatment step may be performed in an inert gas atmosphere or a reducing gas atmosphere. Such a post-treatment heat treatment step may be performed at a temperature above 500°C, for example at about 900°C. The inclusion of a post-treatment heat treatment step may be beneficial, for example, to form deficiencies or defects in the mixed phase oxide, such as inducing oxygen deficiencies, or to perform anion exchange, for example N exchange of O anions, in the formed mixed phase oxide.

[0096] The method can include milling and / or classifying the mixed phase oxide (e.g., impact milling, jet milling, steam jet milling, high energy milling, ball milling, high shear milling, pin milling, air classification, wheel classification, sieving, cyclone separation, bead milling) to obtain a material having any of the particle size parameters listed above.

[0097] The present invention provides a method for producing an electrode, comprising obtaining a mixed phase oxide as defined herein and depositing the mixed phase oxide onto a current collector to form an electrode. Obtaining the mixed phase oxide may comprise synthesizing the mixed phase oxide by the methods provided herein. The depositing step may comprise forming a slurry of the mixed phase oxide and a solvent. The slurry may comprise at least one other component selected from a binder, a conductive additive, a different active electrode material, and mixtures thereof. The slurry may be deposited onto the current collector and the solvent removed to form an electrode layer on the current collector. Optionally, further steps such as heat treatment to cure any binders and / or calendaring of the electrode layer may also be performed. For example, the solvent may be removed by drying, for example, at a temperature of 30-100°C. The electrode may have a density of 2-3.5 or 2.6-2.9 gcm. -3 The thickness of the electrode layer may be in the range of 5 μm to 2 mm, preferably 5 μm to 1 mm, preferably 5 μm to 500 μm, preferably 5 μm to 200 μm, preferably 5 μm to 100 μm, preferably 5 μm to 50 μm.

[0098] Alternatively, the slurry can be formed into a free-standing film or mat comprising the mixed phase oxide, for example, by casting the slurry onto a suitable casting template, removing the solvent, and then removing the casting template. The resulting film or mat is in the form of a coherent, free-standing mass that can then be bonded to a current collector by known methods. EXAMPLES

[0099] The mixed-phase oxides were synthesized by a solid-state route. In the first step, the precursor materials (Nb2O5, TiO2, ZnO, Cr2O3, CuO, MgO, Al2O3, and Ga2O3) were mixed with SiO2 nanoparticles with a diameter of less than 20 μm. 50The powders were then milled to a particle size of 0.01 mm. The appropriate amounts of precursors were then combined and mixed in an impact mill at 20,000 rpm to obtain a homogenous powder mixture (50 g total). The resulting powders were heat treated in alumina crucibles using a muffle furnace for 1-24 hours at 1100-1200 °C depending on the desired Wadsley-Roth phase. Samples 3-12 were removed from the furnace, impact milled at 20,000 rpm, and heated twice using the same conditions. A heating rate of 5 °C / min was used for all heat treatment conditions. If necessary, a final deagglomeration step by impact milling at 20,000 rpm for at least 2 minutes was used to adjust the desired particle size distribution. Particle size distributions were obtained with a Horiba dry powder laser diffraction particle analyzer. Air pressure was kept at 0.3 MPa. The results are shown in Table 1. [Table 1]

[0100] For example, 95TiNb2O7:5Cr 0.6 Zinc 1.6 Nb 33.8 O 87 The expression is 95 parts by weight of TiNb2O7 and 5 parts by weight of Cr 0.6 Zinc 1.6 Nb 33.8 O 87 The term "mixed phase oxide" refers to a mixed phase oxide made from precursors that are weighed to give a mixture of elemental ratios of: In samples 3 to 5, the first phase has a crystal structure of TiNb2O7 but further contains Cr and / or Zn, and the second phase is Zn2Nb 34 O 87 but further containing Cr and / or Ti, In sample 6, the first phase has a crystal structure of TiNb2O7 but further contains Al and / or Zn, and the second phase is Zn2Nb 34 O 87 but further containing Al and / or Ti, In sample 7, the first phase has a crystal structure of TiNb2O7 but also contains Cr, and the second phase is Zn2Nb 34 O 87 but containing Cr and / or Ti, In sample 8, the first phase has a crystal structure of TiNb2O7 but further contains Cr and / or Al, and the second phase is Zn2Nb 34 O 87 but containing Cr, Al, and / or Ti; In sample 9, the first phase has a crystal structure of TiNb2O7 but further contains Ga and / or Al, and the second phase is Zn2Nb 34 O 87 but containing Ga, Al, and / or Ti; In sample 10, the first phase has a crystal structure of TiNb2O7 but further contains Cu and / or Ga, and the second phase has a crystal structure of Zn2Nb 34 O 87 but containing Cu, Ga, and / or Ti; In sample 11, the first phase has a crystal structure of TiNb2O7 but also contains Zn, and the second phase is Zn2Nb 34 O 87 but further containing Ti, In sample 12, the first phase has a crystal structure of TiNb2O7 but further contains Mg and / or Cr, and the second phase is Zn2Nb 34 O 87 It has a crystal structure of 0.01g / g, but contains Mg, Cr, and / or Ti. [Table 2]

[0101] The advantages of the synthesis of the examples herein are that the reference systems TiNb2O7 and 95TiNb2O7:5Ti2Nb 10 O 29These data were collected from a Rigaku SmartLab SE powder X-ray diffractometer using a variable temperature heating stage where the unreacted sample was heated at 6°C / min and an XRD scan was taken every 2 min. The results are presented in Table 2. The synthesis of samples 3 and 5 reached completion at temperatures below 1200°C as indicated by the absence of anatase peaks, whereas the synthesis of samples 1* and 13* did not. After heat treatment of samples 1* and 13* at 1200°C for 12 hours, the synthesis of sample 13* reached completion, whereas the synthesis of sample 1* did not. This is evidenced by the presence of the rutile TiO2(110) peak in the XRD pattern of sample 1*. These data show that the present invention improves the synthesis efficiency of the samples, which facilitates more cost-effective manufacturing.

[0102] Material characterization The phase purity of the samples was analyzed using a Rigaku Miniflex powder X-ray diffractometer over the 2θ range (10-70°) at a scan rate of 1° / min. Figure 1 shows the measured XRD diffraction patterns of samples 1-8. Table 3 presents the crystal structure parameters obtained from the refinement of the XRD patterns of each sample. The first phase, with a crystal structure of TiNb2O7, was found to have peaks at the same positions consistent with ICDD entry 00-039-1407 (space group I12 / m1) (with some shifts of up to about 0.2° due to crystal changes). Zn2Nb 34 O 87 A second phase with a crystal structure of was found to have peaks at the same positions consistent with ICDD database entry 00-013-0317 (space group A12 / m1) (with some shifts of up to about 0.2° due to crystallographic changes). Sample 2 was refined using a combination of both monoclinic (A12 / m1) and orthorhombic (Amma-PDF card 04-021-7859) crystal structures. The second phase of the mixed phase oxide was refined using only the monoclinic crystal structure. The peak shifts compared to the reference database entry for the "base" crystal structure were consistent with the ...34 O 87 The mass ratios of the first and second phases resulting from the refinement were found to be in good agreement with the ratios predicted based on the amounts of the precursors, again with small differences reflecting the predicted substitution elements.

[0103] Sample 3 was subjected to TEM-EDX analysis, which showed a uniform distribution of cations throughout the observed particles, with no localization of the cations to specific domains, confirming the presence of an interpenetrating mixture of the first and second phases, with the simultaneous replacement of the "base" phase. [Table 3] [Table 4]

[0104] Electrochemical characterization The charge rate of Li-ion batteries is usually expressed as "C-rate". A 1C charge rate means a charging current such that the cell is fully charged in 1 hour, while a 10C charge means that the cell is fully charged in 1 / 10 of an hour (6 minutes). The C-rate here is defined from the reversible capacity seen by the anode within the voltage limits imposed by the second delithiation cycle, i.e., 1.0 mAh cm within the voltage limits of 1.1 to 3.0 V. -2 For an anode with a capacity of 1.0 mA cm, the 1C rate is 1.0 mA cm. -2This corresponds to an applied current density of 1000 mA / g active material. For the typical materials described herein, this corresponds to approximately 250 mA / g active material. For analysis, electrochemical testing was performed in half coin cells (CR2032 size). In half coin testing, active materials are tested at the electrode against a Li metal electrode to evaluate the basic performance of the active material. In the following examples, the active material composition to be tested was combined with N-methylpyrrolidone (NMP), carbon black (Super P) acting as a conductive additive, and poly(vinyl difluoride) (PVDF) binder, and mixed into a slurry in a laboratory scale centrifugal planetary mixer. The non-NMP composition of the slurry was 92 wt% active material, 5 wt% conductive additive, and 3 wt% binder. The slurry was doctor blade coated onto an Al foil current collector to the desired coating weight of 69-75 g m. -2 The electrodes were then coated with 2.6–2.9 g cm−1 at 80°C and dried by heating. -3 The electrodes were then calendered to a density of 0.01 mm to achieve a target porosity of 30-35%. The electrodes were punched to the desired size and combined with separator (Celgard porous PP / PE), Li metal, and electrolyte (1.3M LiPF6 in EC / DEC) in a steel coin cell case and sealed under pressure. Cycling was then performed between 1.1 and 3.0 V at low current rates (C / 10) at 25°C for two full cycles of lithiation and delithiation. The current density was then increased to test the cell's capabilities. During these tests, the cells were subjected to asymmetric cycling at 25°C with slow lithiation (C / 5) followed by increasing rates of delithiation (e.g., 5C, 10C) to obtain capacity. Data are averaged from 3-5 cells prepared from the same electrode coating, with errors shown from standard deviation. Thus, the data represents a robust study showing the improvements achieved by the material according to the invention compared to conventional materials. These data are shown in Table 5. [Table 5]

[0105] Consideration It was found that the interpenetrating mixture of the first and second phases, as well as the simultaneous substitution of the "base" phase, resulted in a surprising improvement in the properties of the mixed-phase oxides compared to either of the single phases. In particular, at high rates above 5C, the delithiation specific capacity of Samples 3-5 (mixed-phase oxides containing Nb, Ti, Cr, and Zn) was significantly higher than that of Sample 1* (TiNb2O7) and Sample 2* (Cr 0.6 Zinc 1.6 Nb 33.8 O 87 ), which represents a synergistic improvement. Similarly, the delithiation specific capacity at 5C or higher of each of Sample 6 (mixed phase oxide containing Nb, Ti, Al, and Zn), Sample 7 (mixed phase oxide containing Nb, Ti, and Cr), Sample 8 (mixed phase oxide containing Nb, Ti, Cr, and Al), Sample 9 (mixed phase oxide containing Nb, Ti, Ga, and Al), Sample 10 (mixed phase oxide containing Nb, Ti, Cu, and Ga), Sample 11 (mixed phase oxide containing Nb, Ti, and Zn), and Sample 12 (mixed phase oxide containing Nb, Ti, Mg, and Cr) was found to be higher than both Sample 1* and Sample 2*.

[0106] It is expected that similar advantages will be demonstrated for the range of elements M(III) and M(II) described.

Claims

1. 1. A mixed phase oxide for use as an active electrode material, comprising: the mixed phase oxide comprises Nb and Ti, and further comprises M(III) and / or M(II); M(III) is selected from Cr, Al, Ga, and mixtures thereof; M(II) is selected from Zn, Cu, Mg, and mixtures thereof; the mixed phase oxide comprises an interpenetrating mixture of a first phase and a second phase; The first phase is TiNb 2 O 7 and the second phase has a crystal structure of Zn 2 Nb 34 O 87 The mixed phase oxide has a crystal structure of

2. 2. The mixed phase oxide of claim 1, wherein the XRD pattern of the mixed phase oxide exhibits a peak A at 2θ=26.0±0.1°, which is assigned to the first phase.

3. 10. The mixed phase oxide of any preceding claim, wherein the XRD pattern of the mixed phase oxide exhibits a peak B at 2θ=24.9±0.1°, which is assigned to the second phase.

4. Intensity I of the peak B B The intensity I of the peak A A The ratio of I B / I A ≦0.4, or 0.01≦I B / I A ≦0.25, or 0.05≦I B / I A ≦0.22, or 0.07≦I B / I A 4. The mixed phase oxide of claims 2 and 3, wherein ≦0.

16.

5. 10. The mixed phase oxide of any preceding claim, wherein the weight ratio of the first phase to the second phase is from 199:1 to 1:1, or from 99:1 to 3:1, or from 50:1 to 8:

1.

6. 10. The mixed phase oxide of any preceding claim, wherein the first phase forms at least 85% by weight, or at least 90% by weight, or at least 92% by weight of the mixed phase oxide.

7. 10. The mixed phase oxide of any preceding claim, wherein the first phase and the second phase form at least 80%, at least 90%, or at least 95% by weight of the mixed phase oxide.

8. 10. The mixed phase oxide of any preceding claim comprising 66-80 at.% Nb, 33-17 at.% Ti, and further comprising >0-1 at.% M(III) and / or >0-2 at.% M(II), for all cations.

9. 10. The mixed phase oxide of any preceding claim, wherein the amount of the combination of M(III) and M(II) is > 0.05 at%, or > 0.5 at%, or > 0.6 at%, relative to the amount of Nb.

10. 10. The mixed phase oxide of any preceding claim, wherein the atomic ratio of Ti:Nb is at least 0.3:1, or at least 0.4:1, or from 0.42:1 to 0.5:

1.

11. 10. A mixed phase oxide according to any preceding claim, comprising M(III) or comprising M(III) and M(II).

12. 10. The mixed phase oxide of any preceding claim, wherein M(III) is Cr, Al, and mixtures thereof, and M(II) is Zn.

13. 10. The mixed phase oxide of any preceding claim, wherein M(III) is Cr, Al, and mixtures thereof, or M(III) is Cr.

14. 10. The mixed phase oxide of any preceding claim, wherein M(II) is Zn, Cu and mixtures thereof, or M(II) is Zn.

15. 10. The mixed phase oxide of any preceding claim comprising M(III) and M(II), wherein M(III) is Cr and M(II) is Zn.

16. The mixed phase oxide is in particulate form, and optionally the mixed phase oxide has a D in the range of 0.1 to 100 μm, or 0.5 to 50 μm, or 1 to 20 μm. 50 2. The mixed phase oxide of any preceding claim having a particle size of:

17. The mixed phase oxide has a thickness of 0.1 to 100 m 2 / g, or 0.25 to 50 m 2 / g, or 0.5 to 20 m 2 3. The mixed phase oxide of any preceding claim, having a BET surface area in the range of 0.15 / g.

18. 10. The mixed phase oxide of any preceding claim, wherein the mixed phase oxide has a crystallite size greater than 180 nm, or greater than 200 nm, or greater than 225 nm, or greater than 250 nm.

19. and further comprising at least one additional element, optionally comprising: (i) Zr, Hf, V, Fe, Ta, Mo, W, Mn, Co, Ni, Cd, B, Si, Sn, P, and mixtures thereof; or (ii) Zr, V, Fe, Mo, W, Mn, Co, Ni, Cd, B, Si, P, and mixtures thereof; or (iii) Zr, V, Fe, Mo, W, P, and mixtures thereof.

20. 20. The mixed phase oxide of claim 19, wherein the at least one additional element is present in a total amount of < 5 at%, or < 1 at%, or < 0.5 at%, relative to the amount of Nb.

21. (i) F, Cl, Br, I, N, S, Se and mixtures thereof; or (ii) F, Cl, N, S, and mixtures thereof; or 2. The mixed phase oxide of any preceding claim, further comprising (ii) at least one electronegative element selected from F, N, and mixtures thereof.

22. 22. The mixed phase oxide of claim 21 , wherein the at least one electronegative element is present in a total amount of ≦5 at% or ≦1 at%, relative to the amount of O.

23. 10. The mixed phase oxide of any preceding claim, wherein the interpenetrating mixture of the first phase and the second phase does not form a core / shell structure.

24. 10. The mixed phase oxide of any preceding claim, wherein the mixed phase oxide is coated with carbon.

25. 25. A composition comprising the mixed phase oxide of any of claims 1 to 24 and at least one other component, optionally wherein the at least one other component is selected from a binder, a solvent, a conductive additive, a different active electrode material, and mixtures thereof.

26. 25. An electrode comprising as an active electrode material the mixed phase oxide according to any one of claims 1 to 24.

27. 27. The electrode of claim 26, wherein the mixed phase oxide forms at least 25%, at least 50%, or at least 75% by weight of the total active electrode material of the electrode, or the mixed phase oxide is the only active electrode material of the electrode.

28. 28. The electrode of claim 26 or claim 27, further comprising at least one other component selected from a binder, a conductive additive, a different active electrode material, and mixtures thereof.

29. 30. The electrode of claim 28, wherein the different active electrode materials are selected from lithium titanium oxide, titanium niobium oxide, different mixed phase oxides, graphite, hard carbon, soft carbon, silicon, doped and / or carbon coated versions thereof, and mixtures thereof.

30. 30. A metal-ion battery comprising an electrode according to any of claims 26 to 29, optionally wherein the metal-ion battery is a lithium-ion battery and said electrode forms the anode.

31. 31. The metal-ion battery of claim 30, wherein the lithium-ion battery has a reversible anode active material specific capacity of greater than 230 mAh / g at 23 mA / g, wherein the battery can be charged and discharged at current densities for the anode active material of 230 mA / g or greater, or 1000 mA / g or greater, or 2000 mA / g or greater, or 4000 mA / g or greater, while retaining more than 70% of the initial cell capacity at 23 mA / g.

32. 25. Use of a mixed phase oxide as claimed in any of claims 1 to 24 as an active electrode material in a metal ion battery, optionally in the anode of a lithium ion battery.

33. A method for manufacturing an electrode, comprising the steps of: Obtaining a mixed phase oxide according to any one of claims 1 to 24, and depositing the mixed phase oxide onto a current collector to form the electrode.

Citation Information

Patent Citations

  • Active electrode material comprising a mixed niobium oxide

    CA3192011A1

  • Active material, electrode, secondary battery, battery pack and vehicle

    JP2019169343A